Analysing effective social media communication in higher education institutions - Paul Capriotti; Ileana Zeler (Humanities & Social Sciences Communications, 2023)
Abstract This paper aims to analyse the institutional communication of universities on social media by conducting a content analysis of the communication strategy of 70 higher education institutions (in the United States, Europe and Latin America). The study focuses on three social networks (Facebook, LinkedIn and Twitter) and the analysis three dimensions of social media institutional communication: posting, interactivity and content. Findings reveal that while most universities demonstrate a passive centripetal performance to posting, there is a significant divergence in relation to the level of activity. The study highlights that interactivity focus is predominantly characterised by monologues, despite institutions increasingly integrating various communication resources to foster stakeholder interaction. The majority of universities tend to prioritize exclusive or dominant content combination, with organizational content exhibiting a significantly greater presence. By an integrated analysis of these three key dimensions on social media, this paper this paper offers valuable insights for both academics and practitioners. It contributes to the scholars by facilitating further academic research on social media institutional communication and provides professionals with a practical guide for strategically managing communication on social media.